Assessment of mental workload states in monitors using functional near-infrared spectroscopy. - Wang, Yuzhen; Yu, Ruifeng; Shi, Tongyu (Work, 2025)
Background: As technology develops rapidly and complex systems become more widespread, the study of mental workload (MWL) for monitors has become increasingly important. Objective: To explore the signaling features of functional near-infrared spectroscopy (fNIRS) in different MWL states. Methods: Twenty participants performed the N-back task and fNIRS data were collected to measure changes in blood oxygenation levels in the prefrontal cortex. Additionally, performance metrics and NASA Task Load Index (NASA-TLX) questionnaire results were recorded. Results: NASA-TLX scores increased progressively from 0-back (M = 8.750) to 1-back (M = 34.792), 2-back (M = 52.292), and 3-back (M = 75.625). Significant differences were observed in oxygenated hemoglobin (HbO) concentrations (F 3, 57 = 10.557, p < 0.001) across these tasks. HbO increased from 0-back (M = -0.008) to 1-back (M = -0.002) and 2-back (M = -0.001), but decreased to 3-back (M = -0.002). Channels CH16, CH17, and CH18, located in the left dorsolateral prefrontal cortex (DLPFC), were significantly activated in the 1-back, 2-back, and 3-back conditions. CH1 and CH2, which are located in the right DLPFC, showed significant activation in both the 2-back and 3-back tasks. Conclusions: Our results showed that different levels of the N-back tasks triggered different MWL states. Significant differences in HbO concentrations and activated channels were observed across tasks with varying MWLs. HbO followed an "inverted U" pattern, increasing as the MWL shifted from underload to normal, and subsequently decreasing as it reached overload. Additionally, the left DLPFC was activated earlier than the right DLPFC, with the latter gradually engaging as the MWL increased. This study provides valuable insights into the assessment of MWL states.